Routinizing Charisma: The Rise of Gus and the Transformation of Pesantren in Jepara, Indonesia - Amaliyah, Efa Ida (Jurnal Sosiologi Reflektif, 2025)
Islamic boarding schools (pesantren) in Indonesia serve as influential socio-religious institutions deeply rooted in tradition and community life. Central to their continuity is the figure of the kiai, whose charismatic authority historically shapes both religious practice and institutional governance. This study aims to examine the sociological consequences of leadership transmission from kiai to gus, particularly how this transmission of charisma drives institutional transformation in response to global challenges. Employing a qualitative case study design, the research was conducted at Pesantren Al-Mustaqim in Jepara, Central Java. Data were collected through semi-structured interviews, participant observation, and documentation. Four informants were selected using purposive sampling, consisting of one gus (as the key informant), one alumni, and two members of the local community. Data analysis followed Miles and Huberman’s interactive model, encompassing data condensation, data display, and conclusion verification. The findings reveal that the hereditary transmission of leadership functions as a mechanism for both preserving charismatic legitimacy and introducing adaptive educational reforms. The gus emerges not merely as a successor, but as a transformative agent who bridges traditional Islamic pedagogy with institutional modernisation. The implication of this study is the importance of the routinization of charismatic authority from kiai to gus, which not only strengthens the cultural foundations of the pesantren but also enables for the adaptation of Islamic education to meet the demands of global challenges. Pesantren merupakan lembaga sosial-keagamaan yang berpengaruh dan berakar kuat dalam tradisi dan kehidupan masyarakat Indonesia. Keberlanjutan pesantren bertumpu pada peran sentral kiai, yang secara historis memiliki otoritas karismatik dalam membentuk praktik keagamaan dan struktur kelembagaannya. Penelitian ini bertujuan untuk mengkaji konsekuensi sosiologis dari proses transmisi kepemimpinan dari kiai ke gus, khususnya bagaimana transmisi kharisma ini mendorong transformasi kelembagaan dalam merespon tantangan global. Dengan menggunakan metode kualitatif berupa studi kasus, penelitian ini dilakukan di Pesantren Al-Mustaqim di Jepara, Jawa Tengah. Data dikumpulkan melalui: wawancara semi-terstruktur, observasi partisipan, dan dokumentasi. Empat informan dipilih dengan menggunakan teknik purposive sampling, yang terdiri dari satu gus (sebagai informan kunci), satu alumni, dan dua anggota masyarakat setempat. Analisis data mengikuti model interaktif Miles dan Huberman, yang mencakup kondensasi data, tampilan data, dan verifikasi kesimpulan. Temuan penelitian mengungkapkan bahwa transmisi kepemimpinan yang berlangsung secara turun-temurun berfungsi sebagai mekanisme untuk melestarikan legitimasi kharismatik dan mengawali proses pendidikan yang lebih adaptif. Gus muncul bukan hanya sebagai penerus, tetapi sebagai agen transformatif yang menjembatani pedagogi Islam tradisional dengan modernisasi kelembagaan. Implikasi dari penelitian ini adalah pentingnya  proses rutinisasi kharisma dari kiai ke gus yang tidak hanya akan semakin memperkuat akar budaya pesantren, tetapi juga membuka ruang adaptasi proses pendidikan Islam yang lebih adaptif terhadap tantangan global.